Role of temperature on the cyclic fatigue resistance of thermally treated NiTi files - Emre Ovsay; Ayfer Atav; Taher AlOmari; Anuj Bhardwaj (Annali di Stomatologia)
Objectives: This study aimed to evaluate the impact of body temperature on the cyclic fatigue resistance of two NiTi rotary systems; Fanta Rising (FR; Fanta Dental Materials, China) and FKG Race Evo (REV; FKG Dentaire, Switzerland). Methods: A total of 60 instruments were divided into two groups (n=30 per group) based on the instrument type REV (25/04) and FR (25/04) and then divided into two subgroups according to testing temperature (room and body temperature). The tests were performed using a custom-made stainless-steel artificial canal with a 120° angle and a 5-mm radius of curvature. Instruments were rotated continuously until fracture occurred. Time to fracture (TTF) and number of cycles to fracture (NCF) were recorded for all groups. Statistical analyses were conducted using one-way ANOVA and Tukey’s post hoc tests for intergroup comparisons, and an unpaired t-test for intragroup comparisons. Results: The cyclic fatigue tests revealed that the FR exhibited significantly higher TTF and NCF values compared to the REV ( P < 0.05). There were no significant difference in TTF and NCF at body temperature compared to room temperature ( P > 0.05). Conclusions: The FR files demonstrated superior performance in TTF tests, likely due to its CM heat-treated wire, which enhances durability and user comfort. Body temperature did not effected TTF and NCF of tested instruments.